News on the battle of Petrovaradin and the siege of Belgrade in the autobiographical writings of Jean-frédéric Diesbach - Elezović, Dalibor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper is based on data from the handwritten autobiography of Jean-Frédéric Diesbach, which is kept in the Historical Archives in Fribourg, Switzerland, and in which the Battle of Petrovaradin and the siege of Belgrade are discussed. Diesbach, a Swiss nobleman who was originally in the Swiss and French military service, was later transferred to the Austrian army. This well-known European military leader finished his career as a governor of Syracuse in Sicily and a Major General of the Austrian army. A segment of his memories provides a brief description of the Battle of Petrovaradin and the operations of the Austrian army during the siege of Belgrade. Although it is part of the manuscript of a few pages, it has the value of a historical source, because it is the testimony of participants in these events.